Upper-crustal architecture and record of Famatinian arc activity in the Sierra de Narváez and Sierra de Las Planchadas, NW Argentina - Lusk, Alexander D. (2021)
The 495 to 450 Ma Famatinian orogen, exposed throughout central and northwestern Argentina, formed from east-directed subduction under the Gondwanan margin. The Sierra de Narváez and Sierra de Las Planchadas preserve a rare upper-crustal section of the Famatinian arc. New mapping, structural analysis, detrital U–Pb zircon geochronology, as well as major and trace element geochemistry in the Sierra de Narváez – Las Planchadas are presented to give a comprehensive geodynamic portrait of the volcano-sedimentary, igneous, and deformational processes acting within the top of the Famatinian arc in the Ordovician. Field observations and bulk rock geochemistry agree with previous work indicating that the top of the Famatinian arc consisted of volcanic centers, mafic and felsic feeders, and plutons built into continental crust in a shallow marine arc setting, characterized by fossil-bearing, fine-grained marine sediments interbedded with coarse-grained volcanic-clastic material. Trace element chemistry is consistent with the Sierra de Narváez – Las Planchadas region being a continuation along the main arc axis from the more southerly Sierra de Famatina, not a back arc setting as previously interpreted. Detrital zircon geochronology in Permian and Carboniferous sedimentary units unconformably overlying Ordovician units adds further constraints to the duration of Famatinian arc activity and the source of sedimentary material. Two peaks in detrital zircon ages within Carboniferous and Permian strata at 481 Ma and from 474 to 469 Ma, record periods of enhanced magma addition during Famatinian arc activity. Structural analysis establishes both Famatinian and post-Famatinian (largely Andean) deformation; contractional deformation in the Ordovician, although small relative to middle- to lower-crustal levels of the Famatinian orogen, caused crustal thickening and likely initiated surface uplift. Unlike the Famatinian middle to lower crust, however, where widespread ductile deformation is ubiquitous, shortening here is accommodated by open folding, pressure solution, and likely localized brittle faulting. We briefly speculate on the implications of variable shortening recorded at different crustal levels.